2019
DOI: 10.1371/journal.pmed.1002830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of community health volunteer home visits on child diarrhea and fever in the Volta Region, Ghana: A cluster-randomized controlled trial

Abstract: Background Although there is mounting evidence demonstrating beneficial effects of community health workers (CHWs), few studies have examined the impact of CHW programs focused on preventing infectious diseases in children through behavior changes. We assessed the preventive effects of community health volunteers (CHVs), who receive no financial incentive, on child diarrhea and fever prevalence in Ghana. Methods and findings We conducted a cluster-randomized controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…A trial in Malawi found that volunteer counselling delivered through home visits led to a significant reduction in reported infant cough, fever, and diarrhoea [ 31 ]. A recent trial in Ghana reported that home visits from community health volunteers reduced child diarrhoea and fever in communities with high coverage and regular household contacts of effective duration [ 32 ]. A trial in India of home visits by community-based workers failed to demonstrate an effect on child cough, fever, or diarrhoea prevalence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A trial in Malawi found that volunteer counselling delivered through home visits led to a significant reduction in reported infant cough, fever, and diarrhoea [ 31 ]. A recent trial in Ghana reported that home visits from community health volunteers reduced child diarrhoea and fever in communities with high coverage and regular household contacts of effective duration [ 32 ]. A trial in India of home visits by community-based workers failed to demonstrate an effect on child cough, fever, or diarrhoea prevalence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 The literature also provides evidence that CHVs play an important role in the dissemination of health information in communities. 24 , 25 However, a rapid review of the literature does not identify any study showing the use of a job aid and the role of CHVs in diffusion of FP information to male partners specifically. This finding is important because the job aid may increase male partners support of contraceptive use and be a tool for engaging men in FP—an important strategy for improving reproductive health and gender equality.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not measure progression or severity of disease, which may link health care utilisation to survival in the pathway of change, and this is a limitation. In Ghana, home visits by volunteer CHWs focusing on health education, but who also tested febrile children for malaria and treated childhood diarrhoea with ORS, had no effect on the prevalence of these illnesses (primary outcomes) or case detection/management, compared to no volunteer CHWs [ 36 ]. Although our trial also did not find expected reductions in the prevalence of these illnesses, we did find that recommended case management of iCCM illnesses doubled during our intervention of paid, professional CHWs, compared to baseline.…”
Section: Discussionmentioning
confidence: 99%